Answer:
See explanation
Step-by-step explanation:
1.
[tex](a+b)(a^2-ab+b^2)=a^3-a^2b+ab^2+a^2b-ab^2+b^3=a^3+b^3[/tex]
2.
[tex](1-7x)(1+9x)=1+9x-7x-63x^2=-63x^2+2x+1[/tex]
3.
[tex](x+y+3)(x+y-4)=x^2+xy-4x+xy+y^2-4y+3x+3y-12=x^2+2xy+y^2-x-y-12[/tex]
4.
[tex](a-b)(a^2+ab+b^2)=a^3+a^2b+ab^2-a^2b-ab^2-b^3=a^3-b^3[/tex]
5.
[tex](m^3n+8)(m^3n-5)=(m^3n)^2-5m^3n+8m^3n-40=m^6n^2+3m^3n-40[/tex]
6.
[tex](4-(3c-1))(6-(3c-1))=(4-3c+1)(6-3c+1)=(5-3c)(7-3c)=35-15c-21c+9c^2=9c^2-36c+35[/tex]
7.
[tex](ab-9)(ab+8)=(ab)^2+8ab-9ab-72=a^2b^2-ab-72[/tex]
8.
[tex](a+b-c)(a+b+c)=a^2+ab+ac+ab+b^2+bc-ac-bc-c^2=a^2+b^2-c^2+2ab[/tex]
9.
[tex](a+3)(a-2)=a^2-2a+3a-6=a^2+a-6[/tex]
10.
[tex](3m^3-y)(3m^3-y)=(3m^3)^2-3m^3y-3m^3y+y^2=9m^6-6m^3y+y^2[/tex]
11.
[tex](2x-3y)(4x-y)=8x^2-2xy-12xy+3y^2=8x^2-14xy+3y^2[/tex]
12.
[tex](x^2+2x-1)(x^2+2x+5)=x^4+2x^3+5x^2+2x^3+4x^2+10x-x^2-2x-5=x^4+4x^3+8x^2+8x-5[/tex]
13.
[tex](4x-3y+5)(x+2y-3)=4x^2+8xy-12x-3xy-6y^2+9y+5x+10y-15=4x^2+5xy-6y^2-7x+19y-15[/tex]